Angiopoietin-like 4 Interacts with Matrix Proteins to Modulate Wound Healing - Goh, Yan Yih (American Society for Biochemistry and Molecular Biology, 2010)
A dynamic cell-matrix interaction is crucial for a rapid cellular response to changes in the environment. Appropriate cell behavior in response to the changing wound environment is required for efficient wound closure. However, the way in which wound keratinocytes modify the wound environment to coordinate with such cellular responses remains less studied. We demonstrated that angiopoietin-like 4 (ANGPTL4) produced by wound keratinocytes coordinates cell-matrix communication. ANGPTL4 interacts with vitronectin and fibronectin in the wound bed, delaying their proteolytic degradation by metalloproteinases. This interaction does not interfere with integrin-matrix protein recognition and directly affects cell-matrix communication by altering the availability of intact matrix proteins. These interactions stimulate integrin- focal adhesion kinase, 14-3-3, and PKC-mediated signaling pathways essential for effective wound healing. The deficiency of ANGPTL4 in mice delays wound re-epithelialization. Further analysis revealed that cell migration was impaired in the ANGPTL4-deficient keratinocytes. Altogether, the findings provide molecular insight into a novel control of wound healing via ANGPTL4-dependent regulation of cell-matrix communication. Given the known role of ANGPTL4 in glucose and lipid homeostasis, it is a prime therapeutic candidate for the treatment of diabetic wounds. It also underscores the importance of cell-matrix communication during angiogenesis and cancer metastasis.